Atonal, Senseless, and Abdominal-A regulate rhomboid enhancer activity in abdominal sensory organ precursors. - Witt, L.M.; Gutzwiller, L.M.; Gresser, A.L.; Li-Kroeger, D.; Cook, T.A.; Gebelein, B. (Developmental Biology, 2010)
The atonal (ato) proneural gene specifies different numbers of sensory organ precursor (SOP) cells within distinct regions of the Drosophila embryo in an epidermal growth factor-dependent manner through the activation of the rhomboid (rho) protease. How ato activates rho, and why it does so in only a limited number of sensory cells remains unclear. We previously identified a rho enhancer (RhoBAD) that is active within a subset of abdominal SOP cells to induce larval oenocytes and showed that RhoBAD is regulated by an Abdominal-A (Abd-A) Hox complex and the Senseless (Sens) transcription factor. Here, we show that ato is also required for proper RhoBAD activity and oenocyte formation. Transgenic reporter assays reveal RhoBAD contains two conserved regions that drive SOP gene expression: RhoD mediates low levels of expression in both thoracic and abdominal SOP cells, whereas RhoA drives strong expression within abdominal SOP cells. Ato indirectly stimulates both elements and enhances RhoA reporter activity by interfering with the ability of the Sens repressor to bind DNA. As RhoA is also directly regulated by Abd-A, we propose a model for how the Ato and Sens proneural factors are integrated with an abdominal Hox factor to regulate region-specific SOP gene expression.